1998
DOI: 10.1146/annurev.micro.52.1.191
|View full text |Cite
|
Sign up to set email alerts
|

SOMETHING FROM ALMOST NOTHING: Carbon Dioxide Fixation in Chemoautotrophs

Abstract: The last decade has seen significant advances in our understanding of the physiology, ecology, and molecular biology of chemoautotrophic bacteria. Many ecosystems are dependent on CO2 fixation by either free-living or symbiotic chemoautotrophs. CO2 fixation in the chemoautotroph occurs via the Calvin-Benson-Bassham cycle. The cycle is characterized by three unique enzymatic activities: ribulose bisphosphate carboxylase/oxygenase, phosphoribulokinase, and sedoheptulose bisphosphatase. Ribulose bisphosphate carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
222
0
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(235 citation statements)
references
References 190 publications
5
222
0
8
Order By: Relevance
“…This raises two interesting questions: how many different metabolic processes occur within protein-bound organelles and how widely distributed are such organelles in nature? Electron microscopy has shown that carboxysomes are produced by a number of photo-and chemoautotrophic bacteria (11,12,33 ). In addition, based on bioinformatic studies it appears that Desulfitobacterium hafniense and Desulfovibrio desulfuricans also have the potential to produce a polyhedral organelle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This raises two interesting questions: how many different metabolic processes occur within protein-bound organelles and how widely distributed are such organelles in nature? Electron microscopy has shown that carboxysomes are produced by a number of photo-and chemoautotrophic bacteria (11,12,33 ). In addition, based on bioinformatic studies it appears that Desulfitobacterium hafniense and Desulfovibrio desulfuricans also have the potential to produce a polyhedral organelle.…”
Section: Discussionmentioning
confidence: 99%
“…However, carboxysomes and the S. enterica organelles differ in a number of ways. Carboxysomes function to enhance autotrophic growth at low CO 2 concentrations (2,21,25,33), and the carboxysomes of Halothiobacillus neapolitanus (which are the best studied) consist of a protein shell composed of at …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Possible LysR transcriptional regulator binding sites were defined as TNA-N 7/8 -TNA (Shively et al, 1998;Woodger et al, 2007;Nishimura et al, 2008). The most likely À 10 transcriptional start site was based on Synechocystis PCC 6803 data, most commonly 5 0 -TAAAAT-3 0 (Mitschke et al, 2011).…”
Section: Comparison Of Sequence Datamentioning
confidence: 99%
“…Molecular oxygen is often depleted within the upper few millimeters of the sediments (Sweerts et al 1989), creating a steep chemical gradient that provides a microenvironment with high chemoautotrophic potential (Shively et al 1998). Processes of ammonium, sulfur, and methane oxidation are examples of some redox reactions associated with chemosynthesis in lake sediments (EnrichPrast et al 2009).…”
mentioning
confidence: 99%